Role of Red Cell Distribution Width in Prognosis of Patients of All Age Groups with Sepsis- A Narrative Review - Ghimire, Rajan (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Introduction: Sepsis is life threatening emergency situation that is frequently encountered in every emergency department. Knowing the prognosis of such patient is crucial which is difficult in the busy emergency rooms. There are lots of prognostic tools in practice and red cell distribution width is newer tool that is under test to predict prognosis of patients with sepsis. In recent day different scientific papers are published over red cell distribution width (RDW) in association with sepsis. This article tried to review such articles and give the holistic view of RDW in association with sepsis. Method: Articles were searched in Pubmed, Google scholar, The Cochrane Library, Scopus and Hinari. 26 articles were found and thorough revision of articles was done.Result: Most of the articles point towards overwhelming efficacy of RDW in sepsis across all age group. It can also be used in septic patients with anemia and who received blood transfusions recently. Only few papers are published involving pediatric population and patients with anemia and recent blood transfusion history.Conclusion: RDW is efficacious tool than currently practiced tools to predict prognosis of patient with sepsis across all ages. There are only few studies in pediatric population and patients with anemia and history of recent blood transfusion, so caution is advised while applying RDW among pediatric population and in patients with anemia and recent blood transfusion.